It All Depends What You Count-The Importance of Definitions in Evaluation of CF Screening Performance - Natasha Heather; Dianne Webster (MDPI AG, 2020)
Screening metrics are essential to both quality assessment and improvement, but are highly dependent on the way positive tests and cases are counted. In cystic fibrosis (CF) screening, key factors include how mild cases of late-presenting CF and CF screen positive, inconclusive diagnosis (CFSPID) are counted, whether those at prior increased risk of CF are excluded from the screened population, and which aspects of the screening pathway are considered. This paper draws on the New Zealand experience of almost forty years of newborn screening for CF. We demonstrate how different definitions impact the calculation of screening sensitivity. We suggest that, to enable meaningful comparison, CF screening reports should clarify what steps in the screening pathway are included in the assessment, as well as the algorithm used and screening target.